EDITORIAL (Latin American Journal of Sedimentology and Basin Analysis, 2021)
As you all may have noticed by now, changes have been introduced in the conformation of the editorial team of the Latin American Journal of Sedimentology and Basin Analysis (LAJSBA). Since March 2009 we have been appointed as the Editor (Gonzalo Veiga) and Associate Editor (Alfonsina Tripaldi) for this journal. We would like to thank the Board of the AsociaciónArgentina de Sedimentología (AAS) for honouring us with this task and it is a great commitment for us to continue with the great job that previous editors have done in producing this publication. Both of us have some experience in running this journal as we have been Associate Editors of the former AAS revista at different times, but the mission of being responsiblefor the production of this journal, that for the past 15 years has become a recognised means for publishing sedimentolgy-related research for Latin American specialists is challenging and stimulating.